UNDERSTANDING THE ROLE OF SDG AWARENESS IN SHAPING SUSTAINABILITY ATTITUDES - Afreen Jan; Mohd. Muzamil (ShodhKosh: Journal of Visual and Performing Arts, 2024)
Unlocking the path to sustainable futures requires an understanding of the interaction between awareness and attitudes towards Sustainable Development. To better understand how students perceive sustainability, we looked at the ideas of 267 Kashmir university students in this study. Their attitudes are found to be strong (M=3.56, SD=0.29) and their levels of awareness are excellent (M=3.41, SD=0.37), with what our findings portray as a positive picture. In addition, this correlation is established between attitudes and awareness as (r=0.58, p<0.01), thus clarifying how the two are interconnected. Interestingly, these feelings are gender-neutral. These findings throw light on how education changes lives and prepares a generation for supporting the SDGs. Results also reveal the pressing need to craft pro-sustainability attitudes through education, an increased role of sustainability education within university curricula for the creation of future leaders in sustainable development who are knowledgeable and involved. We plant some seeds of a more equitable and environmentally aware future by adding sustainability into academic discourse.